Future trade research areas that matter to developing country policymakers : a regional perspective on the Doha Development Agenda and beyond 2026-02-12T03:38:42+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (ESCAP studies in trade and investment ;, 2007)

(untitled)
This volume is a collection of papers and commentaries addressing current problems faced by trade policymakers, presented at the Post-Doha Research Agenda for Developing Countries Workshop in October 2006. The workshop was organized cooperatively by ESCAP and WTO as one of the first activities under the new project, the Macao regional Knowledge Hub in Support of Sustainable Trade and development (MARKHUB) sponsored by the government of Macao. Concern is expressed regarding some areas that might become problematic, such as preferential rules of origin, non-tariff barriers and behind-the border barriers.--Publisher's description